2009
DOI: 10.1002/mop.24144
|View full text |Cite
|
Sign up to set email alerts
|

A 77‐GHz six‐port FMCW collision avoidance radar sensor with baseband analytical calibration

Abstract: CPW line and realized by LTCC process for smaller size. The size of the miniaturized antenna is about 8 ϫ 15 mm 2 . As a result, we obtained the stop band from 4.8 to 6.3 GHz. The proposed antennas are good candidates for UWB systems where stop band is needed.ABSTRACT: A 77-GHz six-port frequency modulated continuous wave collision avoidance radar sensor is proposed. Velocity and range are determined from the slope of the instantaneous phase of radar beat signals. Digital signal processing techniques are devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…These RF components are interconnected in such a way that four different vector sums of the reference signal and signal to be directly measured (or up/downconverted) are produced [8]. After processing two signals in the radio-frequency (RF) domain, the results are down converted to baseband.…”
Section: Design Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…These RF components are interconnected in such a way that four different vector sums of the reference signal and signal to be directly measured (or up/downconverted) are produced [8]. After processing two signals in the radio-frequency (RF) domain, the results are down converted to baseband.…”
Section: Design Proceduresmentioning
confidence: 99%
“…A complete theory, validated by various simulations and measurements of direct conversion receivers, has been published in recent years [8][9][10][11][12][13][14][15]. A schematic of six-port structure is shown in Fig.…”
Section: The Narrow Band Six-port Demodulatormentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers then found that the six-port technique could be used for communication transceivers [2][3][4], direction finding receivers [5] and ranging receivers [6][7][8][9], etc.…”
Section: Introductionmentioning
confidence: 99%